Analysing population structure of Elaeis Oleifera germplasm using model-based approach programme STRUCTURE / Wan Nurhayati Wan Hanafi …[et al.] - Wan Hanafi, Wan Nurhayati; Mohd Yusof, Farida Zuraina; Singh, Rajinder; Din, Ahmad Kushairi; Nookiah, Rajanaidu; Ithnin, Maizura (Universiti Teknologi MARA Shah Alam, 2017)
Elaeis oleifera serves as a source of genetic foundation in oil palm improvement programme, as it possess several interesting agronomic traits such as slow growth, higher oil unsaturation and disease resistance. Malaysian Palm Oil Board (MPOB) has developed a collection of simple sequence repeats (SSRs) from Elaeis oleifera genome (E. oleifera-gSSRs). A total of 21 polymoprhic SSR markers were evaluated in the attempt to assess the population structure of E. oleifera populations. The appropriate common ancestry (K) value was determined to be seven from the likelihood scores. The profile from STRUCTURE analysis indicates considerable sharing of genetic components among E. oleifera population with an exception for Population 01 from Columbia and Population 02 from Costa Rica. The present study provides information on population structure of MPOB E. oleifera collection via model-based method for germplasm conservation and utilisation in breeding programmes.